H. PYLORI INFECTION, ENDOSCOPIC, HISTOLOGICAL ASPECTS AND CELL PROLIFERATION IN THE GASTRIC MUCOSA OF PATIENTS SUBMITTED TO ROUX-EN-Y GASTRIC BYPASS WITH CONTENTION RING: a cross sectional endoscopic and immunohistochemical study - NOGUEIRA,Thiago De Bortoli (2016)
ABSTRACT Background Morbid obesity treatment through vertical gastroplasty Roux-en-Y gastric bypass initially used a contention ring. However, this technique may create conditions to the development of potentially malign alterations in the gastric mucosa. Although effective and previously performed in large scale, this technique needs to be better evaluated in long-term studies regarding alterations caused in the gastric mucosa. Objective To analyze the preoperative and postoperative endoscopic, histological and cell proliferation findings in the gastric antrum and body mucosa of patients submitted to the Roux-en-Y gastric bypass with a contention ring. Methods We retrospectively evaluated all patients submitted to Roux-en-Y gastric bypass with a contention ring with more than 60 months of postoperative follow-up. We compared the preoperative (gastric antrum and body) and postoperative (gastric pouch) gastric mucosa endoscopic findings, cell proliferation index and H. pylori prevalence. We evaluated cell proliferation through Ki-67 antibody immunohistochemical expression. Results In the study period, 33 patients were operated with the Roux-en-Y gastric bypass using a contention ring. We found a chronic gastritis rate of 69.7% in the preoperative period (gastric antrum and body) and 84.8% in the postoperative (gastric pouch). H. pylori was present in 18.2% of patients in the preoperative period (gastric antrum and body) and in 57.5% in the postoperative (gastric pouch). Preoperative cell proliferation index was 18.1% in the gastric antrum and 16.2% in the gastric body, and 23.8% in the postoperative gastric pouch. The postoperative cell proliferation index in the gastric pouch was significantly higher (P=0.001) than in the preoperative gastric antrum and body. Higher cell proliferation index and chronic gastritis intensity were significantly associated to H. pylori presence (P=0.001 and P=0.02, respectively). Conclusion After Roux-en-Y gastric bypass with contention ring, there was a higher chronic gastritis incidence and higher cell proliferation index in the gastric pouch than in the preoperative gastric antrum and body. Mucosa inflammation intensity and cell proliferation index in the postoperative gastric pouch were associated to H. pylori presence and were higher than those found in the preoperative gastric antrum and body mucosa.